Comparing different methods to fix and to dehydrate cells on alginate hydrogel scaffolds using scanning electron microscopy. Issue 7 (14th April 2015) - Santana, Bianca Palma; Nedel, Fernanda; Perelló Ferrúa, Camila; e Silva, Ricardo Marques; da Silva, Adriana Fernandes; Demarco, Flávio Fernando; Lenin Villarreal Carreño, Neftali
ABSTRACT Scanning electron microscopy (SEM) is commonly used in the analysis of scaffolds morphology, as well as cell attachment, morphology and spreading on to the scaffolds. However, so far a specific methodology to prepare the alginate hydrogel (AH) scaffolds for SEM analysis has not been evaluated. This study compared different methods to fix/dehydrate cells in AH scaffolds for SEM analysis. AH scaffolds were prepared and seeded with NIH/3T3 cell line; fixed with glutaraldehyde, osmium tetroxide, or the freeze drying method and analyzed by SEM. Results demonstrated that the freeze dried method interferes less with cell morphology and density, and preserves the scaffolds structure. The fixation with glutaraldehyde did not affect cells morphology and density; however, the scaffolds morphology was affected in some level. The fixation with osmium tetroxide interfered in the natural structure of cells and scaffold. In conclusion the freeze drying and glutaraldehyde are suitable methods for cell fixation in AH scaffold for SEM, although scaffolds structure seems to be affected by glutaraldehyde. Microsc. Res. Tech. 78:553–561, 2015. © 2015 Wiley Periodicals, Inc.